Clarification of yeast cell suspensions by a highly porous polyamide nanofiber sponge - Mousavi, S.; Filipová, L.; Ebert, J.; Heiligtag, F.J.; Daumke, R.; Loser, W.; Ledergerber, B.; Frank, B.; Adlhart, C. (Separation and purification technology, 2022)
[Display omitted] •Synthesis of highly porous and flexible polyamide-6 nanofiber sponge (PA6 NFS).•Application of the PA6 NFS as dead-end depth filter.•High clarification efficiency and high flow at low differential pressure.•Modelling of NFS blocking mechanism for applications in liquid filtration.•Filtration performance compared with nanofiber mats and commercial depth filters. Depth filtration is an attractive method for initial clarification of broth for removing cells and cell debris. Electrospun nanofibers with their large specific surface area and a porous structure are known as attractive materials in filtration processes. However, dead-end filtration of cells through nanofiber mats (NFM) always leads to cake formation and increasing resistance. In this study, for the first time, a nanofiber sponge (NFS) or nanofiber aerogel was synthetized from polyamide 6 (PA6) building blocks. The NFS was flexible, highly porous and mechanically stable. The pore size of the NFS was tuned between 8 and 26 µm during the cryogenic processing step. Volumetric flux and filtration efficiency of the NFS depended on the pore size and the results were compared with those for NFM from the same PA6 nanofiber material. Dead-end filtration of Saccharomyces cerevisiae was feasible at a low differential pressure of 3.5 kPa and cell filtration efficiency was > 99 %. Modelling of the filtration process revealed that cake formation is prevented by NFS filters since cells are able to penetrate into the filter and to adsorb on their internal surface. The filtration characteristics were also compared with commercial depth filters and revealed the high flux of NFS filters along with the possibility to avoid filter aids and a low environmental impact. PA6-NFS filters may become a new and cost effective generation of filters for removing different cells or cell debris from broth and other applications.